Kajian Legal Drafting Urgensi Perubahan Peraturan Presiden Tentang Jaminan Kesehatan - Slamet Riyanto; Siti Nur Intihani (VERITAS, 2023)
Law Number 40 of 2004 concerning the National Social Security System (UU SJSN) and Law Number 24 of 2011 concerning BPJS (UU BPJS) order further regulation of the technical aspects of administering the national health insurance program in a Presidential Regulation.In 2018 it was deemed necessary to refine the Presidential Regulation regarding Health Insurance and finally it was replaced by Presidential Regulation concerning Health Insurance Number 82 of 2018 concerning Health Insurance.In addition to the problems above, based on the legal drafting study, it was found that several contents of Presidential Regulation Number 82 of 2018 were disharmony with the Social Security Law and the BPJS Law, there were inconsistent formulation of norms in arrangements between articles, there were repeated arrangements(redundant) so that it is less useful, as well as the existence of ambiguous or multiple interpretations of editorial norms.The problems above are common reasons for the need to make changes to Presidential Regulation Number 82 of 2018 concerning Health Insurance. Specifically, the changes are intended to continue to encourage sustainability and improve the quality of the JKN program.For changes related to the standard inpatient class (KRIS), for example, the review was carried out as mandated by RI Presidential Regulation Number 64 of 2020 concerning the Second Amendment to Presidential Regulation Number 82 of 2018 concerning Social Security.DJSN together with related stakeholders has carried out a series of processes for reviewing and preparing policies including learning from various countries, defining standard inpatient class criteria, identifying the impact of financing and so on.Meanwhile, in order to make KRIS a success, health stakeholders continue to improve cross-sector outreach and coordination.As stated in the mandate of RI Presidential Regulation Number 64 of 2020 concerning the Second Amendment to Presidential Regulation Number 82 of 2018 concerning Health Insurance, the implementation of KRIS is one of the policies in the design of JKN program benefits based on Basic Health Needs (KDK).